Immune checkpoint inhibitors in HCC: Cellular, molecular and systemic data. (November 2022) - Harkus, Uasim; Wankell, Miriam; Palamuthusingam, Pranavan; McFarlane, Craig; Hebbard, Lionel
Highlights: HCC is a poorly treated cancer and its incidence is increasing rapidly worldwide. The combination of checkpoint inhibitors and anti-angiogenic therapy has improved survival in patients with unresectable HCC. Some patients respond well to checkpoint inhibitors, but many attain no benefit or in some cases progress. Modulating the immune response in HCC patients may be beneficial for improving response to checkpoint inhibitor therapy. Numerous clinical trials are underway to develop more personalised HCC therapy. Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer related deaths in the world, and for patients with advanced disease there are few therapeutic options available. The complex immunological microenvironment of HCC and the success of immunotherapy in several types of tumours, has raised the prospect of potential benefit for immune based therapies, such as immune checkpoint inhibitors (ICIs), in HCC. This has led to significant breakthrough research, numerous clinical trials and the rapid approval of multiple systemic drugs for HCC by regulatory bodies worldwide. Although some patients responded well to ICIs, many have failed to achieve significant benefit, while others showed unexpected and paradoxical deterioration. The aim of this review is to discuss the pathophysiology of HCC, the tumour microenvironment, key clinical trials evaluating ICIs in HCC, various resistance mechanisms to ICIs, and possible ways to overcome these impediments to improve patient outcomes.